Frequency of Congenital Hypothyroidism in Newborn at Tertiary Care Hospital in Quetta - Abdul Baqi Essazai, Zakaullah Kakar, Syed Moeed Ahmed, Naseeb Ullah, Pir Jan, Najeebullah (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of congenital hypothyroidism (CH) in newborn at tertiary care hospital in Quetta, Pakistan. Study design: Cross-sectional study. Place and Duration: The Department of Paediatrics, Unit-II, Bolan Medical College Hospital, Quetta, Pakistan from January 2022 to June 2022. Methodology: Neonates of both genders born with birth weight above 1500 grams having gestational age above 28 weeks, presenting between 3 to 5 days following birth were analyzed. At the time of enrollment, demographic characteristics of the neonates were noted and screening of CH was done. The CH was labeled as serum TSH ≥ 20mU/ml and T4 < 9 pmol/l. Results: During the study period, a total of 383 neonates as per inclusion/exclusion criteria were analyzed. There were 239 (62.4%) boys and 144 (37.6%) girls. The mean age was 3.87+0.843 days. The mean TSH level was 12.807+5.11 mU/ml (ranging 7 to 50 mU/ml). We noted that CH was found in 10 neonates (2.6%). Practical Implications: The reported frequency of CH seems higher as compared to contemporary literature which raises the importance of CH screening programs at national level. Conclusion: The frequency of congenital hypothyroidism was 2.6% among newborns at a tertiary care hospital of Quetta, Pakistan. Keywords: Congenital hypothyroidism, newborn, thyroid-stimulating hormone